The sustainability of the dehesas - Gómez Cabrera A.; De Pedro Sanz E. (Mediterranean livestock production: uncertainties and opportunities, 2008)
An analysis of the productive systems used in 'dehesa' grazing lands confirms that the highest quality products come from Iberian pigs that have been fed on acorns. Furthermore, this productive system also offers the best prospects for sustainability. However, there are currently two factors that could condition this situation in the relatively short term: on the one hand, the deterioration of oak trees as the result of oak decline ('seca') and an absence of natural regeneration caused by intensive systems; and on the other hand, market competition with Iberian pork produced using intensive farming methods. Faced with these challenges there are several possible courses of action, mainly focusing on oak reforestation and the establishment of classification and traceability methods that ensure clear differentiation of products on the market. This paper deals with our efforts to create georeferenced records for oak trees using GIS tools, which include compositional and nutritional information about the acorns produced. Our research into quality differentiation systems for Iberian pig carcasses and pork products using NIRS technology is also discussed. This paper considers the viability of the various courses of action and the feasibility of simultaneously considering environmental and cultural alternatives.
2. Seminar of the Scientific-Professional Network on Mediterranean Livestock Farming (RME), 2006/05/18-20, Zaragoza, (Spain)